2016
DOI: 10.1007/s12185-016-2047-6
|View full text |Cite
|
Sign up to set email alerts
|

Pure red cell aplasia induced by anti-erythropoietin antibodies, well-controlled with tacrolimus

Abstract: Anti-erythropoietin (anti-EPO) antibody-related pure red cell aplasia (PRCA) is a rare but serious complication that can occur during the administration of erythropoiesis-stimulating agents. Treatment with the calcineurin inhibitor cyclosporine has shown benefits in patients with anti-EPO PRCA. The efficacy of tacrolimus, another calcineurin inhibitor, in patients with anti-EPO PRCA has not been determined. The present report is the first our knowledge to describe the successful treatment of a patient with ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…T-LGL-associated PRCA. Tacrolimus showed activity as a salvage option in a few reports, 37 , 38 and we were able to substantiate those findings in our study. While no head-to-head comparisons were conducted, previous reports suggested lower response rates to CTX vs .…”
Section: Discussionsupporting
confidence: 88%
“…T-LGL-associated PRCA. Tacrolimus showed activity as a salvage option in a few reports, 37 , 38 and we were able to substantiate those findings in our study. While no head-to-head comparisons were conducted, previous reports suggested lower response rates to CTX vs .…”
Section: Discussionsupporting
confidence: 88%
“…Recently, studies had recommended initial treatment, including cyclosporine or cyclophosphamide combined with prednisone in PRCA ( 9 , 11 , 20 ). Tacrolimus may be considered as a substitute for cyclosporine ( 21 ). Chen et al.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies had recommended initial treatment, including cyclosporine or cyclophosphamide combined with prednisone in PRCA (9,11,20). Tacrolimus may be considered as a substitute for cyclosporine (21). Chen et al also reported the therapeutic effect of sirolimus in PRCA patients with a complete response of 58.3% and a median time of 4 (1-7) months to achieve the optimal effect (22).…”
Section: Discussionmentioning
confidence: 99%
“…Especially, the peak incidence of PRCA related to ESA therapy occurred during 2002–2003 [ 1 ]. The majority of those cases were caused by a preparation of epoetin-alfa (Eprex/Erypo) [ 5 , 6 ], though a small case series caused by epoetin-beta was also reported [ 7 10 ]. This transient increase of PRCA related to Eprex during 2002–2003 was associated with the use of the polysorbate-80(PS-80) formulation in prefilled syringes with uncoated rubber stoppers [ 6 , 11 ].…”
Section: Introductionmentioning
confidence: 99%